Maternal Education and Children Home Alone in 63 Low- and Middle-Income Countries - Toufica Sultana MA; Mónica Ruiz-Casares PhD; René Iwo MA; Magdalena Janus PhD; José Ignacio Nazif-Muñoz PhD (SAGE Publishing, 2024)
Background. Maternal education may influence child supervision practices in low-and middle-income countries (LMIC). However, little is known about the maternal factors that can improve child supervision in LMIC with scarce childcare facilities. Objective. To investigate the prevalence of children under 5 years home alone and examine the association between mother's formal education and children home alone across 63 LMIC. Methods. The study used data from 50 Multiple Indicator Cluster Surveys and 13 Demographic and Health Surveys with a sample of 501 769 children. We estimated Prevalence Ratios (PRs) for the association between maternal education and children home alone using multivariable Poisson regression, adjusting for covariates such as child's age and sex, mother's age and marital status, number of adults inhabiting the households, and urbanicity. Results. Prevalence of children home alone across 63 LMIC ranged from 1.1% to 50.1%. A significant negative association between mothers with more years of formal education and children home alone was found across 16 LMIC. However, the opposite trend was observed in Nigeria, Senegal, and Côte d'Ivoire. Null association was found across 44 LMIC. Conclusions. The varied pattern of the associations observed across LMIC underscores the importance of regional and local factors when developing policies and interventions to ensure safety and adequate care for children aged under 5 years in LMIC.